Skills for green jobs: 2018 update : European synthesis report - (:unkn) unknown (Publications Office of the European Union, 2019)
"Preparing for sustainable growth within the context of a circular economy is an accepted policy aim across the globe. The implications for economic sectors, and consequently for occupations, skills and relevant policies, are undeniable. In 2010 Cedefop collaborated with the International Labour Organization and reviewed the state of play regarding 'green skills' and 'green jobs' in six EU countries (Denmark, Germany, Spain, Estonia, France and the UK). A European synthesis report built on the six country reports. In 2017, the collaboration was repeated to ascertain progress made since 2010: this report provides a synthesis of the six new country reports. It examines the major changes in green jobs and employment since 2010, and analyses the regulations and policies supporting green skills and employment, including the surrounding institutional set-up and the role played by social partners. It also highlights good practices, including green skill anticipation mechanisms, relevant vocational education and training and higher education, active labour market policies and retraining measures, and the role of the private sector." (Publisher, BIBB-Doku)
Keywords: G 1.2 Arbeitsmarkt; S 6.4.8.1 Umweltberufe; G 1.2.3 Qualifikationsentwicklungen; I 2.2.1 Westeuropa; I 2.2.2 Osteuropa; Arbeitsmarktentwicklung; Wirtschaftsentwicklung; Green skills / grüne Kompetenzen; Qualifikationsentwicklung; Umweltberuf; Berufsbildungspolitik; Dänemark; Estland; Spanien; Frankreich; Vereinigtes Königreich; Bundesrepublik Deutschland